DOI: 10.26481/dis.20180111mh
|View full text |Cite
|
Sign up to set email alerts
|

A patient perspective on eHealth in primary care

Abstract: Document Version:Publisher's PDF, also known as Version of record Please check the document version of this publication:• A submitted manuscript is the version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…Our results are in line with available evidence on patient perspective for E-Health technology in other health disciplines relative to its positive impact on access, treatment adherence, cost-effectiveness, health outcomes, satisfaction, empowerment and quality of life [ 34 , 37 42 ]. Moreover, these studies on e-health also reported patients’ willingness to use and learn such technology, also similar to this present study [ 3 , 34 36 , 40 , 41 ]. Furthermore, patients’ concerns regarding E-Oral Health were also consistent with that of E-Health technology in terms of lack of human contact and personal data privacy [ 34 , 43 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our results are in line with available evidence on patient perspective for E-Health technology in other health disciplines relative to its positive impact on access, treatment adherence, cost-effectiveness, health outcomes, satisfaction, empowerment and quality of life [ 34 , 37 42 ]. Moreover, these studies on e-health also reported patients’ willingness to use and learn such technology, also similar to this present study [ 3 , 34 36 , 40 , 41 ]. Furthermore, patients’ concerns regarding E-Oral Health were also consistent with that of E-Health technology in terms of lack of human contact and personal data privacy [ 34 , 43 ].…”
Section: Discussionsupporting
confidence: 88%
“…Patient participation is imperative even earlier in order to effectively design, implement and utilize E-Health technology. A deep understanding of patient needs regarding the use of E-Health and E-Oral Health will aid in these efforts [34]. Patient perspectives on E-Oral Health have been measured among a wide range of patients utilizing the health services in both developed and developing nations, such as in general private and public health services, primary health care services, rehabilitation services and services for multi-morbid chronic diseases [3,[34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Modern persuasive technologies (e.g. applications) offer the possibility to enhance goal setting and provide tailored information to people with OA that suits individual preferences and to enhance self-management at all times [31, 32]. Moreover, modern technologies can monitor health behaviour and provide real-time feedback, which are considered important elements of self-management [15, 33].…”
Section: Introductionmentioning
confidence: 99%